Enkulturasi Kesenian Tradisional Andung di Sanggar Seni Budaya Tunas Kelapa Samosir - Panggabean, Ente Lina; Evelin Limbong, Helena; Hardiarini, Caecilia (Jurnal Penelitian Musik, 2024)
This research aims to describe the process of Enculturation of Traditional Art Andung in Sanggar Seni Budaya Tunas Kelapa Samosir. In the process of enculturation, of course, it has the support of the local government, namely by helping in terms of sanggar needs. Efforts to maintain Andung traditional arts, Sanggar Seni Budaya Tunas Kelapa Samosir also uses social media as a platform that is used to introduce traditional Andung arts such as Youtobe, Facebook and Instagram. The process of Enculturation of Traditional Art Andung occurs through non-formal channels that are through (sanggar) which is held regularly and the training process is carried out at Sanggar Seni Budaya Tunas Kelapa Samosir every Thursday at 14.00 to 17.00 with the arrangement of the Andung art learning process in Sanggar Seni Budaya Tunas Kelapa Samosir starting from the stage, namely: Introducing Andung art, then the students see, and imitate what has been taught by the coach, then the coaching process occurs.  This research uses qualitative descriptive using survey methods; observations, in-depth interviews (indepfh interviews), and documentation